2021
DOI: 10.3906/kim-2009-17
|View full text |Cite
|
Sign up to set email alerts
|

New chlorogenic acid derivatives and triterpenoids from Scorzonera aucheriana

Abstract: Chromatographic separation of n-hexane and ethyl acetate fraction of a crude methanol extract obtained from aerial parts of the Scorzonera aucheriana DC collected from Sivas province of Turkey yielded nine natural compounds, including two new 3caffeoyl-quinic acid analogs (1-2), and one new taraxasterol oleate (3), as well as six known triterpenoids taraxasterol (4), taraxasterol acetate (5), ptiloepoxide (6), lupeol (7), lupeol acetate (8), and β-sitosterol (9) were characterized. The structures of the 2 isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Samples of S. aucheriana were collected in central Turkey and aerial parts were extracted with methanol at room temperature [ 7 , 29 ].…”
Section: Phytochemical Composition Of Scorzonera Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…Samples of S. aucheriana were collected in central Turkey and aerial parts were extracted with methanol at room temperature [ 7 , 29 ].…”
Section: Phytochemical Composition Of Scorzonera Speciesmentioning
confidence: 99%
“…Investigation on aerial parts of the plant led to the isolation of dihydroisocoumarins and dihydroisocoumarin derivatives (scorzopygmaecoside, scorzocreticoside II, iso-scorzopygmaecoside, scorzoaucherioside I and II), quinic acid derivatives (3,5- O -dicaffeoyl- epi -quinic acid and 3,5- O -dicaffeoylquinic acid), and 3,4-dihydroxyphenyl caffeate [ 7 ]. In another study, chlorogenic acid derivatives (methyl 1-(2-methylcyclopropyl-1-carbonyloxy)chlorogenate and 3,4-bis[(3′,4-dioxo-1′,3′,5′,6′-tetrahydrospiro[cyclohexa-2,5-diene-1,4′-cyclopenta[ c ]-furan]-1′-yl)]chlorogenic acid), triterpenoids (taraxasterol, taraxasterol acetate, taraxasterol oleate, lupeol, lupeol acetate and ptiloepoxide) and β-sitosterol were isolated from the methanol extract of S. aucheriana aerial parts [ 29 ].…”
Section: Phytochemical Composition Of Scorzonera Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, results revealed that the majority of the PE fraction is consisted of triterpenoids. Among them, the most abundant peaks belonged to ß‐amyrin, lupeol, 13,27‐cycloursan‐3‐ol‐acetate, two cholestane derivatives, taraxasterol, germanicol, and lupeyl acetate which were previously reported from different Scorzonera species [28,38–40] . Particularly, taraxasteryl acetate, olean‐12‐en‐11‐one‐3‐acetyl, lupeol, and lupeyl acetate were reported from S. incisa collected from a different location, by HPLC‐DAD [28] .…”
Section: Resultsmentioning
confidence: 79%
“…Numerous phytochemical analyses and studies on the biological activity of Scorzonera species have been conducted with regard to the ethnobotanical value of the genus [3,10–12] . Phytochemical studies on Scorzonera species have shown the presence of flavonoids, dihydroisocoumarins, sesquiterpenes, triterpenes, stilbenes, quinic acid, chlorogenic acid, caffeic acid derivatives, and other bioactive compounds [3,7,8,9,11–37] . Biological evaluation of the isolated compounds and extracts/fractions of Scorzonera species was also reported [3,11,12,36–43] …”
Section: Introductionmentioning
confidence: 99%